PENYULUHAN HUKUM TENTANG PEMAHAMAN HUKUM KETENAGAKERJAAN BAGI SISWA DI SMKN 7 PALU - Asri Lasatu; Irzha Friskanov. S (Universitas Kadiri, 2024)
The employment relationship relates to the parties to the employment agreement. Students who will soon complete their upper secondary studies will prepare themselves to enter the world of work. An understanding of the rights and obligations that students must know when entering the world of work. So the problem is how to increase the understanding of employment for secondary students. This service activity provides education to high school students about the importance of knowledge and understanding in labor law, both from the essence of work relations to termination of employment. The location of the service will be carried out at SMKN 7 Palu using the lecture and discussion method. The conclusion is that students still lack knowledge about the rights and obligations of work. The enthusiasm of the students was seen when the students questioned the legal protection for child workers.